LEGAL PERSPECTIVE OF PORN PRODUCTION IN INDIA: A STUDY WITH SPECIAL REFERENCE TO ONLYFAN.COM - Kumar, Sanjeev; Pallathadka, Dr. Harikumar; Klrana Pallathadka, Dr. Laxmi (The journal of contemporary issues in business and government, 2022)
The word "pornography” may be described as the reporting or representation of sexual behaviors in order to elicit sexual arousal via the publication of books, films, or other media, including the internet. In this category are pornographic websites, pornographic content made using computers, and the use of the internet to obtain and send pornographic videos, texts, images, and photographs (among other things). Private viewing porn in India does not constitute a criminal offense under Indian penal laws. Onlyfans' content providers are sexual and pornographic artists who charge a high price for their work.Onlyfans is legal in the United States, Canada, and the United Kingdom, but a few nations have outlawed it entirely. As per Indian legislation, everyone who posts sexual stuff online is regarded as breaking the law, and Onlyfans falls under this category.The current research work aims to draw attention to the association between porn vis-a-vis Onlyfans and criminality. Though it is legal to use Onlyfans, this research paper will cover some legal concerns.